Control of Texture and Morphology of Zinc Films through Pulsed Methods from Additive‐Free Electrolytes. Issue 22 (10th June 2021) - Fuller, Lee; Martin, Jason; Ma, Yuanman; King, Seth; Sen, Sujat
Abstract: We investigate the electrodeposition of zinc on steel substrates using pulsed methods from additive‐free electrolytes in an industrially scalable parallel plate flow cell. We demonstrate that variables such as peak current and duty cycle can be used to independently control the morphology and preferential texture of the crystalline structure, which is, in turn, desirable for a variety of applications. Specifically, we have observed a transition of the preferential (002) facets at low peak current density (or low duty cycle) to (101) preferring facets at higher peak current density (or high duty cycle) as determined by the analysis of texture coefficients. Further analysis using scanning electron microscopy reveals a transition from the conventional hexagonal‐shaped particles of zinc to needle‐shaped structures, accompanied by a change in average crystallite size from 33 to 19 nanometers, determined from X‐ray diffraction studies. The variation in morphology is also correlated to crystallographic textures through the analysis of texture coefficients and an understanding of crystallization mechanisms occurring during deposition. Collectively, these results demonstrate that the morphology and crystalline orientation of zinc can be easily manipulated through tuning of the pulse parameters without the use of complex and expensive additives that have been traditionally used to achieve similar effects. Abstract : Additive‐free electrolytes were used to deposit zinc by tuning the peak current and duty cycle of the pulse process. A transition of the preferential (002) facets at low peak currents to (101) preferring facets at higher peak current was observed, accompanied by a reduction in average crystallite size. These results demonstrate that the morphology and crystalline orientation of zinc can be manipulated without the use of complex and expensive additives that have been traditionally used to achieve similar effects.